Critical Review: Future of Block Chain Economy in Financial Services (Global Journal of Management and Business Research, 2020)
This research paper is based on the future of block chain economy in financial sectors and its significant usage. The researcher emphasized that the block chain technology has the potential to disrupt financial services and it can change the current face of financial Industry. The researcher focused on the significant usage of block chain economy to fraud detection, to maintain the customer's history, trade finance, and smart contracts. There are some challenging faces of block chain economy towards adoption in financial sectors such as interoperability, privacy, energy consumption, security, scalability, and legal regulations. The researcher also stated that block chain economy is a scenario and potential future environment in which crypto currency replaces current monetary systems on a global basis to become an autonomous market participants in financial sectors. The researcher also highlights the key challenges of block chain economy adoption in financial sectors with current statistics of future analysis.
Keywords: block chain economy; financial sectors; crypto-currency